Kepercayaan Ibu Rumah Tangga tentang Nyamuk Aedes dan Pencegahan Demam Berdarah Dengue di Kelurahan Endemis - Aryani Pujiyanti, Ira Paramastri, Atik Triratnawati (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: Active community participation in controlling mosquito breeding sites (Pemberantasan Sarang Nyamuk/PSN) in Semarang especially apart from epidemic situation was difficult to be formed as a habit. It was shown by the high incidence of dengue hemorrhagic fever cases and the larva-free rate that haven’t met the national indicator of 95%. The lack of comprehension about DHF, vector and DHF prevention could be barriers in implementation of DHF prevention. This understanding was connected with local belief and social cultural factors in the community.Objective: To explore housewife’s belief of Aedes mosquitoes that might affect DHF prevention practice in endemic sub district, Tembalang district, Semarang.Method: Research was conducted with qualitative design, using case study. Subject of the study were 17 housewives which selected with purposive sampling. The data collection was carried out through focus group discussions, indepth interviews and observation. The techniques used to test data validity were triangulation and member checking method. Data were analyzed using content analysis approached.Results: Housewives who had small children felt more vulnerable toward DHF. The community would tend to pay attention to the seriousness of the threat when DHF cases were increased in the community. Aedes sp was more perceived as a nuisance rather than disease vectors. Barriers that arise from PSN were the implementation that was not all together and PSN needed specific time and energy.Conclusion: Housewives tend to use a biomedical model for understanding the causes, signs and treatment of critical stage of DHF. Housewives perception of Aedes could be explained by naturalistic model. PSN suggested by health practitioners was not suitable with cultural context. A program that could be suggested was a training of cadres to identify mosquito breeding sites, introduction of mosquito-stage development and the correct practice of 3M plus.Keywords: dengue hemorrhagic fever, belief, housewives, Aedes